Variation in Payment per Work Relative Value Unit for Breast Reconstruction and Nonbreast Microsurgical Reconstruction: An All-Payer Claims Database Analysis. Issue 3 (2nd October 2021) - Shamsunder, Meghana G.; Sheckter, Clifford C.; Sheinin, Avraham; Rubin, David; Berlin, Nicholas L.; Mehrara, Babak; Matros, Evan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Commercial payments for implant-based breast reconstruction have increased within the past decade, whereas reimbursements have stagnated for microsurgical techniques. The physician payment–to–work relative value unit ratio allows for standardization when comparing procedures of differing complexity. This study aimed to characterize payment per work relative value unit for common breast and nonbreast microsurgical procedures. Methods: The Massachusetts All-Payer Claims Database was queried from 2010 to 2014 for Current Procedural Terminology (CPT) codes related to microsurgical and breast reconstruction. International Classification of Diseases codes were further used to categorize procedures by anatomical region, including head and neck, breast, trunk, and extremities. Physician payments, both commercial and governmental, were aggregated by anatomical region and CPT code. Payment distributions were described with means and medians and compared using statistical tests. Results: Among 3435 commercial claims, distributions of physician payments per work relative value unit for microsurgical and common breast procedures differed only for breast free flaps billed through S codes ( p < 0.001). Microsurgical breast procedures (CPT code 19364) had significantly greater median payments per work relative value unit compared to microsurgery of the head and neck, trunk, and upper extremities ( p = 0.004). Payment per work relative value unit for common breast and nonbreast microsurgical procedures did not differ significantly among governmental claims ( p = 0.103). Conclusions: Adjustment of physician payments by work relative value units did not show significant variability across common breast procedures, except for S codes, suggesting that payments are mostly driven by differences in work relative value units and individual contractual negotiations. Lower payments per work relative value unit for other regions compared to breast suggests an opportunity for negotiation with commercial payers.